Heterogeneous Effects of Frontier Technology Readiness on Economic Growth in Africa - Isaac K. Ofori; Emmanuel Y. Gbolonyo; Andrea Vezzulli (ZBW - Leibniz Information Centre for Economics, 2024)
Despite the remarkable growth in frontier technology adoption (FTR) in the Global South, empirical evidence concerning their socioeconomic impacts in the context of Africa is hard to find. This study, therefore, employs macro data for a sample of 39 African countries to bridge three pressing gaps in the growth literature. First, we examine the impact of FTR on economic growth. Second, the study assesses whether FTR and egalitarian democracy synergistically enhance economic growth. Third, this study examines the heterogeneous effects of FTR across growth quantiles. Robust evidence, based on the dynamic system-GMM and the method of moments quantile regression, reveals the following: first, FTR promotes economic growth, but the effect is modest; second, egalitarian democracy amplifies the growth-enhancing impact of FTR, but only at higher thresholds of egalitarianism. Third, although FTR is growth-enhancing across all growth quantiles, the effect diminishes from the 1st to the 9th quantile. However, in the presence of egalitarian democracy, FTR significantly enhances growth across all growth quantiles from the 1st to the 9th. We conclude that progress in egalitarian democracy and investments for enhancing FTR are crucial for economic growth in Africa.
Keywords: O31; O38; O55; Q01; 330; Africa; Economic growth; Democracy; Egalitarian democracy; Frontier technology readiness